Truth, trust, and the bottom line 7 steps to trust-based management - Tracy, Diane (Dearborn Trade, 2001)
Every manager who offers constructive, honest feedback to employees, using these seven steps, will unearth a powerful new management tool. After observing top leaders for years, author-consultants Diane Tracy and William J. Morin have codified these best practices and outline how to tell employees the truth, talk straight with them, and give them the information they need about themselves to skyrocket their performance.